2014
DOI: 10.1111/cts.12167
|View full text |Cite
|
Sign up to set email alerts
|

Research Participant‐Centered Outcomes at NIH‐Supported Clinical Research Centers

Abstract: Background Although research participation is essential for clinical investigation, few quantitative outcome measures exist to assess participants’ experiences. To address this, we developed and deployed a survey at 15 NIH-supported clinical research centers to assess participant-centered outcomes; we report responses from 4,961 participants. Methods Survey questions addressed core aspects of the research participants’ experience, including their overall rating, motivation, trust, and informed consent. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 28 publications
2
42
0
Order By: Relevance
“…Several studies [1,3,[8][9][10] have focused on satisfaction as it relates to participation in research studies and retention of participants throughout the duration of the clinical study. Verheggen et al [8] conducted a survey in the Netherlands using personal interviews and telephone questionnaires and found that patient satisfaction was quite high.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies [1,3,[8][9][10] have focused on satisfaction as it relates to participation in research studies and retention of participants throughout the duration of the clinical study. Verheggen et al [8] conducted a survey in the Netherlands using personal interviews and telephone questionnaires and found that patient satisfaction was quite high.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, participants do not need to continue their participation once they have enrolled in a study but can withdraw without consequences for any reason. Kost et al [1,9,10] hypothesize that improved understanding on the part of the research participant can enhance human subjects' protection, enhance recruitment and retention, improve the quality of the research process, and increase public trust in the overall research enterprise. Thus, a participant-oriented approach to measuring satisfaction with the research process would be comparable to the current standard of evaluation of the clinical performance of hospitals and would be of use to clinical researchers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations